The influence of resilience and social support on mental health of older adults living in community: a cross-sectional study - Ratchaneekorn Upasen; Weeraphol Saengpanya; Wanida Awae; Preedanan Prasitvej (BMC Psychology, 2024)
Abstract Background Mental health is an important fundamental element of health that influences different dimensions of an older individual’s life. There are various factors that affect the mental health of older adults, such as resilience and social support. However, the relationship between various factors and mental health is unclear. Purposes of the study were to investigates whether resilience and social support affect the mental health of older adults and to analyze the structural equation model of mental health among the older adults with resilience as a mediating variable. Methods A cross-sectional study was conducted among 964 older adults by multi-stage random sampling. The data were collected using the following questionnaires: Thai Elderly Resilience Scale, Social Support Scale, and Thai Geriatric Mental Health Assessment. Data analysis used descriptive statistics, Pearson’s correlation, and Path analysis. Results The older adults had a high level of resilience, social support, and mental health (MH). The best model we obtained demonstrated that social support and resilience had directly statistically significant influences the MH. Social support also had statistically significant indirect effect via resilience to the MH. Conclusion Understanding the factors that influence mental health of older adults can be beneficial for health professionals to provide appropriate social support and resilience, including helping the older adult can join with others, be confident in life, have necessities, live with spiritual security, and be able to de-stress and management problems were recommended.